Kajian Serapan N, P dan Hasil Umbi Kentang (Solanum tuberosum L.) pada Berbagai Takaran Phonska Alam di Lahan Kering Sembalun Lombok Timur - Permana, Wahyu Enggal; Sukartono, Sukartono; Kusumo, Bambang Hari; Kusnarta, IGM; Bakti, Lalu Arifin Aria (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Potatoes (Solanum tuberosum L.) are one of the horticultural commodities that have an important role as a food source. The purpose of this study is to determine the nutrient absorption of Nitrogen, Phosphorus and potato tuber products at various doses of natural phonska in the dry land of Sembalun East Lombok. The method used in this study is an experimental method by conducting field experiments that test various doses of natural phonska fertilizer. With fertilizer doses of P0 0 kg/ha, P1 800 kg/ha, P2 1,200 kg/ha, P3 1,600 kg/ha and the use of mulch on potato plants (Solanum tuberosum L.). This research was carried out from March to August 2024, in Sajang Village, Sembalun District on land owned by PT Sembalun Kusuma Emas (SKE). The application of natural phonska and mulch has a real effect on the absorption of nutrients from Nitrogen and Phosphorus. The application of phonska 1,600 kg/ha with mulch application (P3M1) yielded the best absorption value, namely, Nitrogen 1.70 gr/ton and Phosphorus 0.21 gr/ton. The application of natural phonska fertilizer and mulch has a real effect on the number of leaves of potato plants, especially at the age of 3 and 7 weeks after planting (MST). The application of natural phonska fertilizer and the use of mulch have a real effect on the yield of potato plants. The application of phonska 1,600 kg/ha with the application of mulch (P3M).